2021
DOI: 10.1093/plankt/fbab011
|View full text |Cite
|
Sign up to set email alerts
|

Winter zooplankton dynamics in the English Channel and southern North Sea: trends and drivers from 1991 to 2013

Abstract: Winter has long been regarded as a period of minor importance in marine zooplankton ecology with static, low concentrations and growth rates of organisms. Yet, there is growing evidence that winter conditions influence spring bloom strength. With rising water temperatures, growing importance of fish larvae survival during winter and the lack of data to parameterize ecosystem models for this period, research focus shifted on winter zooplankton ecology. To enable looking into past changes in winter zooplankton e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…New available methods may help to shed light on the link between PZP and fish larvae, as the methods used in this study showed some limitations (see "Methodological assessment"). Given the importance of prey (< 300 µm) in larval herring diets (Alvarez-Fernandez et al 2015;Dudeck et al 2021), further studies on this trophic link are needed, as well as considerations to include PZP and MZP monitoring into routine programs to improve current fisheries assessment processes. For example, if PZP and MZP assessments suggest that certain taxa or size classes are directly related to larval growth, they could serve as indicators of good habitat suitability and larval fish performance (e.g.…”
Section: Larvae Spawned In Winter Rely More On Pzp Than Mzp To Cover ...mentioning
confidence: 99%
“…New available methods may help to shed light on the link between PZP and fish larvae, as the methods used in this study showed some limitations (see "Methodological assessment"). Given the importance of prey (< 300 µm) in larval herring diets (Alvarez-Fernandez et al 2015;Dudeck et al 2021), further studies on this trophic link are needed, as well as considerations to include PZP and MZP monitoring into routine programs to improve current fisheries assessment processes. For example, if PZP and MZP assessments suggest that certain taxa or size classes are directly related to larval growth, they could serve as indicators of good habitat suitability and larval fish performance (e.g.…”
Section: Larvae Spawned In Winter Rely More On Pzp Than Mzp To Cover ...mentioning
confidence: 99%